The IPTEACES E-Learning Framework: Success Indicators, the Impact on Student Social Demographic Characteristics and the Assessment of Effectiveness - Pena, N.; Isaias, Pedro (Springer, 2012)
With the publication of Regulatory Rule 17/2006-R, specifically with regard to qualification courses for Insurance Intermediaries – (resulting from an implementation of the EU directive on insurance mediation), it became mandatory for all new insurance intermediaries to attend a certification course. This certification targets a diverse social-demography and geographically dispersed range of attendees. This demanded a new approach to e-learning instructional design. To develop this training and certification solution in an e-learning format (having as a formal requirement a final face-to-face examination), it was considered vital to design a specific and proprietary e-Learning “framework” which could contain in itself the “learning principles” and that it would fit, as far as possible, the diversity and heterogeneity in terms of different ages, gender, educational background, previous knowledge in the area, literacy, computer proficiency, organizational culture, motivations, values and experience/inexperience in e-Learning, etc. This framework, was primarily inspired through a pedagogical benchmark (mainly Gagné ’s Nine Events of instruction (Gagne 1985 ; Gagne et al. 1992 ), Merrill’s Principles of Learning ( 2002, 2007 ) , Keller’s ARCS’s model ( 2008 ) and van Merrienboer’s Ten Steps to Complex Learning (2007)) , as well as in a close observation of award winning ecourses (e.g., Brandon Hall Excellence in Learning Awards, International e-Learning Association Awards) and corporate e-Learning best practices (e.g., Bersin and Associates reports). With this framework in mind, we’ve conceived and designed an instructional design framework that could materialize, largely on a single approach, an appropriate learning strategy for different learners in order to fi t the different learning preferences and also to respect other specific differences.